Effect of steel reinforcement distribution on ultrasonic pulse velocity measurements. Issue 1 (March 2021) - Salah, Muhammad Ali; Al-Rifaie, Ali; Al.Khuzaie, Hussein M. Ashour
Abstract: Non-destructive tests (NDTs) represented one of the solutions that aid the engineers to evaluate the strength of materials. However, the results obtained using such tests still questionable as they may be affected by different factors. One of these factors is the presence of steel reinforcement in concrete. An experimental investigation is presented in the current study to investigate the effect of the distribution of steel reinforcement on the one of the most common NDTs named Ultrasonic Pulse Velocity (UPV). However, two small-scale concrete slabs were tested and the results were successfully obtained. Two different spacing between the longitudinal reinforcement were considered. Also, the effect of measuring the UPV in the top and bottom surface of the RC slab was studied. The effect of direct path length was also investigated. The results showed that the presence of reinforcement considerably affects the UPV values. Besides, no judgement was made to decide the effect of path length as fluctuated results were obtained.